Analysis of HOT Content in the Integrated Thematic Students’ and Teachers’ Handbook of the 2013 Curriculum - Tiyas Arifin; Ali Mustadi; Heri Maria Zulfiati; Anang Fathoni (Universitas Pendidikan Ganesha, 2023)
Higher-order thinking skills (HOTs) are becoming an important skill in today's era. Students’ and teachers’ handbook should have HOT content. This study aims to analyze HOT content in the analysis aspect, evaluation aspect, and creating aspect in the students' and teachers' handbook of the 2013 curriculum on the fifth theme of the third grade. This research used a qualitative approach and content analysis methods. The object was HOT content. Data collection techniques used documentation by reading and taking notes carefully. Validity used semantic validity and reliability used stability and reproducibility. Data analysis techniques consisted of unitizing, sampling, recording/coding, reducing, inferring, and narrating. The findings showed that HOT content has already appeared, but the distribution was not equal. The analysis aspect mostly appears through various questions that can stimulate students' thinking. In evaluation aspect, mostly appears through activities at the end of the lesson. In the creation aspect, most students are commanded to be creative to solve the problem. The result of this study can be used as information for teachers in preparing learning activities by focusing on students' higher-order thinking skills.